2020
DOI: 10.1186/s40621-020-00261-2
|View full text |Cite
|
Sign up to set email alerts
|

Approaching community priorities in youth sports injury prevention research

Abstract: Background: Research in youth sports is often complex. As interest in youth sports injury prevention grows, scientists should consider community priorities beyond a specific research study. Main text: This commentary discusses the authors' personal experiences researching concussion prevention in middle school sports, as the overarching community faced multiple challenges. These challenges included a series of weather-related emergencies that resulted in a shift in the community's priorities, multi-day school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Our study, in line with others (Meehan 3rd and Mannix 2010 ; McCrory et al 2017 ; Haarbauer-Krupa et al 2018 ; Gonzalez et al 2020 ; Kerr et al 2020 ), revealed higher proportions of health care utilization for SRCs among older aged males as compared to females or younger age groups. We speculate that this finding may be due in part to the prevalence of concussion in male dominated sports such as American football (McCrory et al 2017 ; Gonzalez et al 2020 ; Kerr et al 2020 ). Consistent with prior studies (Meehan 3rd and Mannix 2010 ; Haarbauer-Krupa et al 2018 ), we found higher proportions of health care utilization for NSRCs in younger age groups than older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…Our study, in line with others (Meehan 3rd and Mannix 2010 ; McCrory et al 2017 ; Haarbauer-Krupa et al 2018 ; Gonzalez et al 2020 ; Kerr et al 2020 ), revealed higher proportions of health care utilization for SRCs among older aged males as compared to females or younger age groups. We speculate that this finding may be due in part to the prevalence of concussion in male dominated sports such as American football (McCrory et al 2017 ; Gonzalez et al 2020 ; Kerr et al 2020 ). Consistent with prior studies (Meehan 3rd and Mannix 2010 ; Haarbauer-Krupa et al 2018 ), we found higher proportions of health care utilization for NSRCs in younger age groups than older age groups.…”
Section: Discussionsupporting
confidence: 92%